Attitudes towards 12-step groups and referral practices in a 12-step naive treatment culture; a survey of addiction professionals in Norway - Laudet Alexandre; Kristensen Øistein; Vederhus John-Kåre; Clausen Thomas (BMC, 2009)
Abstract Background Addressing substance use disorders effectively requires a long-term approach. Substance abuse treatment is typically of short duration; referring patients to Twelve Step based self-help groups (TSGs) - e.g. Narcotics Anonymous, represents a promising complementary recovery resource. Clinicians' attitudes and referral practices towards the TSGs have mainly been studied in countries with high integration of the 12-step philosophy in their substance abuse services and where the TSGs are widely available, such as the US. In Norway, there are currently 294 weekly TSG meetings (6 per 100,000 inhabitants). This study describes clinicians' attitudes and referral practices to TSGs in Norway where health authorities seek to promote self-help participation, but where the treatment culture is unfamiliar with 12-step fellowships. Methods Data collected by a self-administered questionnaire, adapted from established US and UK instruments. Information covered the attitudes, knowledge and referral practices towards TSGs among addiction treatment professionals in Norway in mid 2008. Results The return rate was 79.7% (n = 291). Participants had moderately positive attitude scores towards TSGs, but referral to these groups among Norwegian addiction professionals was low, as was the level of knowledge about TSGs. More than six out of ten did not refer any patients to TSGs in the previous week. Local variation with more referrals to TSGs in the county with the one established 12-step treatment facility was observed. Respondents' integration of the 12-steps in their own treatment work, higher self-efficacy for making a successful referral, and greater TSG knowledge were associated with referring patients. Conclusion Low referral rates to TSGs point to the need for education and training to raise the awareness and knowledge about it among addiction professionals unfamiliar with these 12-step fellowships. Training should focus on the usefulness of these groups for all types of treatment models regardless of therapeutic orientation. Increased knowledge is expected to lead to higher referral rates, which in turn would maximize the likelihood of positive long-term patient outcomes.